Macroeconomic Policy Effects on Domestic Credit to the Private Sector in Developing Countries - Fitri Yulia Andini; Deswita Herlina; Muhammad Nasim Harahap (Journal of Business and Economics Research (JBE), 2026)
This study analyzes the effects of the federal funds rate, non-performing loans, trade openness, inflation, lending interest rates, and exchange rates on domestic credit to the private sector in 31 small open developing economies during 2010–2024 using the System Generalized Method of Moments (System GMM) approach. The results show that the federal funds rate, non-performing loans, trade openness, inflation, and lending interest rates have a significant negative effect, while the exchange rate has a significant positive effect on domestic credit to the private sector. The finding on trade openness is inconsistent with the initial hypothesis, as it shows a negative coefficient of (−0.063) in the short run and (−0.535) in the long run. The results also indicate that long-run effects are greater than short-run effects. In the long run, the exchange rate has the largest effect with a coefficient of (8.629), while in the short run it also shows the largest coefficient of (1.016). These findings highlight the importance of adaptive macroprudential policies in maintaining credit intermediation stability in developing economies.